Relasi Kuasa Ulama Sufi dan Negara dalam Kultur-Budaya Politik Indonesia - Rubaidi Rubaidi (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2021)
This article examines the critical role of the dimensions of Sufism represented by Sufi ulama in the public sphere (political power) state, either directly or indirectly. In Indonesian historicity, the relationship between Sufi ulama and the state has lasted centuries, even to the modern era. In political theory, there is a "descending of power" and an "ascending of power". Descending power is identical to religiopolitical power, namely power based on religion by placing Sufi scholars as representatives of the people and above the king's power. Power is interpreted as a political system that separates religion and state. This problematic relationship places Sufi ulama in a transcendent way to become part of the state both directly and remotely. Examples of ascending of power are shown clearly through the figures of Habib Lutfi bin Yahya and KH. Maimun Zubair (Mbah Maimun) is in the midst of a potential nation clash during the 2019 presidential election process. This study is based on secondary sources in related references and primary sources. The primary source is based on the thoughts of a Sufi teacher and the murshid of Majelis Shalawat Kubro, Shalawat Muhammad, and Shalawat Adlimiyah in East Java.